2003
DOI: 10.1590/s0036-36342003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Atención médica de lesiones intencionales provocadas por la violencia familiar

Abstract: Atención médica de lesiones intencionales provocadas por la violencia familiar. Salud Publica Mex 2003;45:252-258. El texto completo en inglés de este artículo está disponible en: http://www.insp.mx/salud/index.html ResumenObjetivo. Describir y analizar las características de la demanda provocada por lesiones intencionales, en especial las provocadas por violencia familiar en los servicios de urgencias de hospitales públicos de la Ciudad de México. Material y métodos. Se realizó un estudio transversal, en el c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
6
1
10
Order By: Relevance
“…The present study shows that the majority of women who suffer violence are young, in contrast with other authors, 7,15,[21][22][23] who report on the subject amongst women in age ranges of up to 44. This shows that the women who are beaten in the family environment are probably those with an active sex life, for they weare younger than those considered by other authors.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The present study shows that the majority of women who suffer violence are young, in contrast with other authors, 7,15,[21][22][23] who report on the subject amongst women in age ranges of up to 44. This shows that the women who are beaten in the family environment are probably those with an active sex life, for they weare younger than those considered by other authors.…”
Section: Discussioncontrasting
confidence: 90%
“…Several studies have shown a link between high alcohol consumption and family break ups. 15,22 This substance is consumed on a large scale in Brazil, principally among men, and has an impact on their behavior with negative repercussions for women, and sometimes leading to physical violence.…”
Section: Introductionmentioning
confidence: 99%
“…42 Entretanto, trata-se de uma população de estudo diferente da presente investigação, o que pode contribuir para as diferenças encontradas. Dados oficiais confirmam, para o Paraná e Londrina, a presença das agressões como a terceira causa de internação entre crianças e adolescentes vítimas de causas externas, no ano de 2003.…”
Section: Christine Baccarat De Godoy Martins E Maria Helena Prado De unclassified
“…Estudos nacionais e internacionais apontam para a qualidade da informação como uma questão vital na discussão sobre a violência. 35,42,50 Sendo assim, torna-se essencial o treinamento adequado e contínuo dos recursos humanos envolvidos com a notificação da violência contra menores. O investimento em pessoal especializado pode contribuir para o melhor registro das informações necessárias para que se conheçam as características da criança violentada, seu agressor, as circunstâncias em que ocorrem estas violências, entre outras características vitais para a análise deste importante agravo na população infanto-juvenil.…”
Section: Violência Contra Crianças E Adolescentesunclassified
“…Our research takes place in Mexico, where a large number of studies have been done on the effects of intimate partner violence (Alonso-Castillo et al 2011, Vieyra et al 2009) and domestic violence (Híjar-Medina et al 2003, Saucedo 2009, Valdez 1998. Traditionally, these studies overlook the phenomena of interaction, a core element to understanding the process leading to violence (Ramírez-Rodríguez 2006).…”
Section: Introductionmentioning
confidence: 99%